Pengaruh Model Numbered Head Together terhadap Hasil Belajar PKn Kelas V SDN 15 Padang Sarai - juwita, poppy; reinita, reinita; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at finding out theeffects of the implementation of the‘Numbered Head Together’ model, also known as a Cooperative Learning toward students learning outcomes of the Civics lesson at class V of SDN 15 Padang Sarai. This quasi experiment applied the nonequivalent control group design. The population of this research was all grade V students of SDN 15 Padang Sarai. Class VBwas chosen as the experiment class while class VCwas the control class by using the purposive sampling technique. Based on the data analysis using the t-test with the significant level of 0.05, it is found that tcount>ttablewith the score of tcount= 2.149 whilettable=1.67. Thus, the H1 hypotesis is accepted.Keywords: NHT model, learning outcomes.